2002
DOI: 10.1034/j.1600-0463.2002.100110.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological diagnosis of variant Creutzfeldt‐Jakob disease

Abstract: The neuropathological and biochemical features of the 89 histologically confirmed cases of variant Creutzfeldt‐Jakob disease (vCJD) diagnosed up to the end of October 2001 in the UK are reviewed. Histology of the central nervous system, lymphoid tissues and other organs was accompanied by immunocytochemistry and Western blot analysis of the disease‐associated form of the prion protein (PrPRES). All patients with vCJD were methionine homozygotes at codon 129 of the PrP gene. The pathology of vCJD showed relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
2
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 27 publications
2
54
2
2
Order By: Relevance
“…In 1996, the National CJD Surveillance Unit in Edinburgh reported 10 patients with a new variant form of CJD, which was subsequently referred to as variant CJD (vCJD) [21]. This disorder was identified on the basis of its clinical and pathological features, which have remained relatively uniform since its original description (Table 4) [22,23]. No significant differences exist in the sex incidence of this disease, but the wide age range (12-74 years at onset) has raised questions concerning the adequacy of disease surveillance in the elderly population, particularly in view of the declining autopsy rate in the UK.…”
Section: Variant Cjdmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1996, the National CJD Surveillance Unit in Edinburgh reported 10 patients with a new variant form of CJD, which was subsequently referred to as variant CJD (vCJD) [21]. This disorder was identified on the basis of its clinical and pathological features, which have remained relatively uniform since its original description (Table 4) [22,23]. No significant differences exist in the sex incidence of this disease, but the wide age range (12-74 years at onset) has raised questions concerning the adequacy of disease surveillance in the elderly population, particularly in view of the declining autopsy rate in the UK.…”
Section: Variant Cjdmentioning
confidence: 99%
“…No significant differences exist in the sex incidence of this disease, but the wide age range (12-74 years at onset) has raised questions concerning the adequacy of disease surveillance in the elderly population, particularly in view of the declining autopsy rate in the UK. Pathologically, the disease is characterized by the presence of numerous florid plaques in the cerebral cortex and cerebellum, which are large amyloid plaques composed of PrP Sc , surrounded by spongiform change [23]. In other brain regions, the neuropathological features are variable, but the posterior thalamus consistently shows extensive neural loss and astrocytosis, the distribution of which is reflected in the high signal present in the posterior thalamus in magnetic resonance imaging scans of the brain [24].…”
Section: Variant Cjdmentioning
confidence: 99%
“…As PrP Sc is abundantly accumulated in the brain, brain samples are appropriate for these detection methods, which require post-mortem analysis. Immunohistochemical (IHC) examination of brain sections is a relatively reliable method of prion diagnosis [3,46] in which typical features of prion diseases, such as accumulation of prion protein (PrP) amyloid plaques, astrogliosis, and neuronal cell loss, are examined by light microscopy. Vacuolation is also used as an index of prion infection.…”
Section: Conventional Diagnostic Methods For Prion Diseasesmentioning
confidence: 99%
“…28 It is believed that vCJD possesses distinct clinical and neuropathological characteristics from sporadic CJD (sCJD) and other forms of prion disease in human. 29 The main distinguishing neuropathological feature of vCJD is an extensive deposition of PrP Sc amyloid in the brain in the form of large 'florid' plaques. 30 Other phenotypes include a younger average age of onset, and gliosis of the thalamis.…”
Section: Types Of Prion Diseasementioning
confidence: 99%
“…Therefore, the UK National CJD Surveillance Unit reported that vCJD is caused by exposure to BSE and that the primary source of exposure is the consumption of infected meat products. 29 Unlike vCJD, Iatrogenic CJD is an entirely person to person transmitted disease, identified to be transmitted through a number of mechanisms including contaminated surgical instruments, 33 and dura mater grafts, 34 blood transfusions 35 and injection of products from cadaveric pituitary glands. 36, 37 The first case of iCJD was described in 1974 where a corneal graft recipient died after acquiring a dementialike likness.…”
Section: Types Of Prion Diseasementioning
confidence: 99%